PROSES BERPIKIR SISWA SMK DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN PHLEGMATIS - Rina Agustina; Nurul Farida (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The aims of the research is to describe the thinking process at SMK students to solve matematic problems viewed from personality type phlegmatic. The research was a descriptive qualitative. The subjects of the research was students of class XI SMK Negeri 3 Metro. Technique analyzing of the data were: (1) classifying the, (2) presenting the data, and (3) concluding the data in each categories. The results of the research showed that thinking process for phlegmatic student: (a) understanding information and question, (b) devising solution, connecting the first equation with the planned solution (c) only using one way solution